2021
DOI: 10.1186/s13045-021-01183-2
|View full text |Cite
|
Sign up to set email alerts
|

Response to COVID-19 mRNA vaccination in multiple myeloma is conserved but impaired compared to controls

Abstract: Patients with multiple myeloma are at high risk of severe forms of COVID-19. Despite data showing diminished response to vaccine, the era of highly efficient mRNA vaccine might be a gamechanger. We sought to examine response to mRNA vaccine between healthy controls (n = 28) and multiple myeloma (MM) patients (n = 27). Response was analyzed 1 month after the second dose of anti-SARS-CoV-2 BNT162b2 vaccine. Multiple myeloma patients showed diminished levels of Anti-Spike IgG levels compared to controls, but with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 4 publications
6
16
2
2
Order By: Relevance
“…The rate of antibody non-responders after the first dose was highest in patients with MM (50%) and SOT (28.6%), but improved four weeks after the second dose to 17.1% and 1.6%, respectively. These results underline the importance of completing the two-dose schedule with mRNA vaccines and are in line with data showing diminished seroresponses within one month after the second dose in MM and SOT patients compared to controls ( 18 20 ). Of note, patients with hematooncological cancers such as MM have seroconversion rates compared to SOT patients.…”
Section: Discussionsupporting
confidence: 89%
“…The rate of antibody non-responders after the first dose was highest in patients with MM (50%) and SOT (28.6%), but improved four weeks after the second dose to 17.1% and 1.6%, respectively. These results underline the importance of completing the two-dose schedule with mRNA vaccines and are in line with data showing diminished seroresponses within one month after the second dose in MM and SOT patients compared to controls ( 18 20 ). Of note, patients with hematooncological cancers such as MM have seroconversion rates compared to SOT patients.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, 82 studies were included for meta-analysis ( table 1 , supplementary table 2). 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 …”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies reported specific outcomes for patients in remission 11 , 16-18 , 21-25 , 30 , 31 ( Supplementary Table S2 ). In the pooled analysis of these studies, the patients in remission had lower seroconversion rates than healthy controls, although with a smaller RD (RD: −0.10%, 95% CI: −0.18%, −0.02%, P = .01; Fig.…”
Section: Resultsmentioning
confidence: 99%